Transcriptome analysis of germ cell changes in male Chinese mitten crabs (Eriocheir sinensis) induced by rhizocephalan parasite, Polyascus gregaria - Feng, Chengcheng; Zhang, Jinbing; Bao, Jie; Luan, Daiwei; Jiang, Ning; Chen, Qijun (Frontiers in Marine Science, 2023)
The parasitism by Polyascus gregaria on Eriocheir sinensis induces feminization of the appearance of male crabs, misleading fishermen to bring them to the breeding ponds as female crabs to cultivate broodstock selection. However, there are few studies on whether P. gregaria feminizes the male germ cells, resulting in a decline in the fecundity of male crabs. Therefore, this study aims to clarify the changes in gene expression levels of male crab testes after being parasitized by P. gregaria through transcriptome sequencing to evaluate the change in fecundity. We selected parasitized and healthy male crabs from a pond culture for comparison of gene expression in germ cells. The results showed that, compared with healthy male crabs, there were 104 genes with significantly different expressions, of which 79 were up-regulated and 25 were down-regulated. These genes are mainly focused on the cytoskeleton pathway in cell components and cellular protein complex assembly in biological processes. Several spermatogenesis-related genes, such as Kazal-type protease inhibitor, which inhibits gelatinolytic activities of sperm proteases, and juvenile hormone esterase 6, which degrades methyl farnesoate, were up-regulated; while the down-regulated expression of certain heat shock proteins may lead to spermatogenic dysfunction. In addition, some immune-related genes, such as double whey acidic protein domain-containing protein and serine proteinase inhibitor 3, were significantly up-regulated. These results indicated that P. gregaria changed the development process and cell structure of male host germ cells to inhibit sperm proliferation and maturation, while multiple immune pathways in the hosts were activated to resist P. gregaria invasion.